Comparative Outcomes of On-lay Mesh and Sub-lay Mesh Techniques in Ventral Hernia Repair: A Prospective Study of 140 Patients - Saira Mahmood, Attaullah Mahar, Sunil Dut Suchdev, Shamaila Ayub, Iftikhar Ahmed, Asma Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to compare the outcomes of the on-lay mesh technique and the sub-lay mesh technique for ventral hernia repair. Study Design: Prospective/Comparative Study Place & Duration: Department of General Surgery, Shalamar Medical and Dental College/Hospital Lahore from June 2022 to May 2023. Methods: A total of 140 individuals of both sexes, aged 18 to 75 years, undergoing ventral hernia repair were included in the study. After obtaining the patient’s consent, demographic data, including age and gender, were recorded. The patients were randomly divided into two groups: Group I and Group II. Participants in Group I underwent repair using the on-lay mesh technique, while Group II received the sub-lay mesh approach. Postoperative outcomes, including pain levels, wound infections, seroma formation, and hospital stay duration, were compared between the two groups. Data analysis was performed using SPSS 24. Results: In Group I, the mean age was 47.12 ± 5.38 years, while in Group II, it was 48.7 ± 11.66 years. Of the total patients, 81 (57.8%) were females, and 59 (42.2%) were males. Postoperative pain was significantly higher in Group I (mean 5.1 ± 3.18) compared to Group II (mean 2.9 ± 4.16). Wound infection occurred in 24 (17.1%) patients in Group I and 14 (10%) patients in Group II (p < 0.005). Seroma formation was noted in 16 (11.4%) patients in Group I and 8 (5.7%) patients in Group II (p < 0.005). The average hospitalization duration was significantly longer for patients in Group I (6.0 ± 1.36 days) compared to those in Group II (3.2 ± 0.44 days, p < 0.05). Conclusion: The sub-lay mesh technique for ventral hernia repair proved to be not only effective but also safer, with a lower incidence of complications, reduced postoperative pain, and a shorter hospital stay compared to the on-lay mesh technique. Keywords: On-lay Mesh Technique, Ventral Hernia Repair, Outcomes, Sub-lay Mesh Technique